Air accessibility and the export of Italian manufacture in Europe: Evidence at regional level - Marco Alderighi (European Regional Science Association (ERSA), 2013)
We study the link between air accessibility (measured by non-stop flights offer) and the manufacturing export of the Italian regions in Europe using a panel of 12,000 half-yearly observations ranging from 1998 to 2010. The analysis shows that the supply of non-stop flights provided by full-service carriers has a positive impact on the exports of Italian regions, whilst no significant evidence of this is found for low-cost carriers. This last result may be partially due to a lower *flight frequency offered by low-cost carriers and to the intrinsic features of low-cost carrier business model (*flying to secondary airports, imposing strict baggage restrictions, providing limited seat space, etc.).
Keywords: C23; F10; L20; L60; L93; 330; airlines; export; full-service carriers; low-cost carriers; manufacturing